Superior mesenteric artery-related outcomes in fenestrated/branched endografting for complex aortic aneurysms - Gallitto, E.; Faggioli, G.; Vacirca, A.; Lodato, M.; Cappiello, A.; Logiacco, A.; Feroldi, F.; Pini, R.; Gargiulo, M. (Frontiers in Cardiovascular Medicine, 2023)
Aim Early/follow-up durability of superior mesenteric artery (SMA) stent-grafts is crucial after fenestrated/branched endografting (FB-EVAR) in complex abdominal aortic aneurysms (CAAAs) and thoracoabdominal aortic aneurysms (TAAAs). The study aimed to report early/midterm outcomes of SMA incorporated during FB-EVAR procedures. Methods FB-EVAR procedures performed between 2016 and 2021 in a single institution were reviewed. Anatomical SMA characteristics were analyzed. The SMA configuration was classified into three types according to the angle between the SMA main trunk and the aorta: (A) perpendicular, (B) downward, and (C) upward. SMA-related technical success (SMA-TS: cannulation and stenting, patency at completion angiography without endoleak, stenosis/kinking, dissection, bleeding, and 24-h mortality) and SMA-adverse events (SMA-AEs: one among bowel ischemia, stenosis, occlusion, endoleak, reinterventions, or SMA-related mortality) were assessed. Results Two hundred FB-EVAR procedures with SMA as the target artery were performed. The indication for FB-EVAR was CAAAs and TAAAs in 99 (49%) and 101 (51%) cases, respectively. The SMA configuration was A, B, and C in 132 (66%), 63 (31%), and 5 (3%) cases, respectively. SMA was incorporated with fenestrations and branches in 131 (66%) and 69 (34%) cases, respectively. Directional branch (P < .001), aortic diameter ≥35 mm at the SMA level (P < .001), and ≥2 SMA bridging stent-grafts (P = .001) were more frequent in TAAAs. Relining of the SMA stent-graft with a bare metal stent was necessary in 41 (21%) cases to correct an acute angle between the stent-graft and native artery (39), stent-graft stenosis (1), or SMA dissection (1). Relining was associated with type A or C SMA configuration (OR: 17; 95% CI: 1.8–157.3; P = .01). SMA-TS was achieved in all cases. Overall, 15 (7.5%) patients had SMA-AEs [early: 9 (60%), follow-up: 6 (40%)] due to stenosis (2), endoleak (8), and bowel ischemia (5). Aortic diameter ≥35 mm at the SMA level was an independent risk factor for SMA-AEs (OR: 4; 95% CI: 1.4–13.8; P = .01). Fourteen (7%) patients died during hospitalization with 10 (5%) events within the 30-postoperative day. Emergency cases (OR: 33; 95% CI: 5.7–191.3; P = .001), peripheral arterial occlusive disease (OR: 14; 95% CI: 2.3–88.8; P = .004), and bowel ischemia (OR: 41; 95% CI: 1.9–87.9; P = .01) were risk factors for 30-day/in-hospital mortality. The mean follow-up was 32 ± 24 months; estimated 3-year survival was 81%, with no case of late SMA-related mortality or occlusion. The estimated 3-year freedom from overall and SMA-related reinterventions was 74% and 95%, respectively. Conclusion SMA orientation determines the necessity of stent-graft relining. Aortic diameter ≥35 mm at the SMA level is a predictor of SMA-AEs. Nevertheless, SMA-related outcomes of FB-EVAR are satisfactory, with excellent technical success and promising clinical outcomes during the follow-up.